Evaluation of Hazard Analysis and Critical Control Points Implementation in Milk Collection Centers in Qalyubia Governorate - Atteya, Lamya A.F.; EL-Sayed, Hemat S.; Azab, Dalia M.; Abou-arab, Nasser M.; Mahdy, Zeinab A.M.; Nabil, Mohamed E. (Journal of Advanced Veterinary Research, 2023)
Hazard Analysis and Critical Control Point (HACCP) is a system that concerns with the identification, evaluation and management of risks that have a potential impact on food safety and quality; especially in a highly nutritious yet easily perishable food like milk and dairy products that can be easily contaminated with contain such biological, physical, and chemical hazards. Therefore, this study aimed to evaluate the returns from HACCP implementation in dairy farms and milk collecting centers (MCCs) located in Qalubiya governorate, Egypt through assessment of the quality, safety and potential adulteration in the collected raw milk samples, along with environmental swabbing for the sanitary condition monitoring pre- and post HACCP implementation, which included an overall improvement in sanitary and hygienic quality of milking, transportation, storage, and personnel conditions, along with documentation and traceability processes at the examined farms and MCCs. Statistical analyses were conducted to compare findings before and after a one-month duration of HACCP application. The results revealed a significant improvement (p â‰¤ 0.05) in the physico-chemical and microbiological quality of milk samples at both farm and MCC levels. This improvement directly reflected on the quality and fitness of milk for human consumption. In conclusion, the application of HACCP effectively controlled various hazards during milk production, even adulteration, and improved the hygienic quality of raw milk. Therefore, it is highly recommended for HACCP implementation in milk production facilities, with continuous monitoring for optimal results.